Family Functioning in Adolescents with Perinatal HIV Infection - Orawan Louthrenoo MD; Linda Aurpibul MD; Peninnah Oberdorfer MD, PhD; Virat Sirisanthana MD (Journal of the International Association of Providers of AIDS Care, 2018)
This study aimed to assess family functioning in adolescents with perinatal HIV infection receiving antiretroviral therapy compared with healthy controls. Correlations between self-reported and caregiver-reported family functions were also evaluated. A sample of 195 participants including 65 perinatally HIV-infected adolescents and 130 healthy controls were enrolled. The total family functioning score in HIV-infected adolescents was significantly lower than that in healthy controls by self-report (105.86 vs 115.41; P ≤ .001). Caregivers of HIV-infected adolescents also reported lower scores of family functioning than those of controls (109.91 vs 114.98; P ≤ .001). Among the HIV-infected group, there was no or minimal correlation between the self-reported and caregiver-reported total scores of family functioning. However, there were moderate correlations between self-reported and caregiver-reported family functioning total scores in the control group. Overall, HIV-infected adolescents reported lower family functioning than healthy controls. Improved functioning in the family may help with better adjustment in perinatally HIV-infected adolescents.